Vývojové vztahy mezi paroháči. 3. Jelenci - největší a nejmenší - Pluháček, Jan
The last part of the series on cervid taxonomy involves the subfamily Capreolinae. This subfamily could be divided into two clades: an Old World clade including Roe Deer (Capreolus capreolus, C. pygargus), Chinese Water Deer (Hydropotes inermis) and Moose (Alces alces) and a New World clade including Reindeer (Rangifer tarandus), Mule Deer (the genus Odocoileus) and deer of Mesoamerica and South America (Ozotoceros bezoarticus, Blastocerus dichotomus and species of the genera Hippocamelus, Pudu and Mazama). Most of the species belonging to Capreolinae are evolutionary young. The evolutionary relationships among extant South American deer remain unclear. Cervids are the most successful ungulate family that has ever colonized South America. Jan Pluháček.